Neuropsychological testing of cognitive impairment in euthymic bipolar disorder: an individual patient data meta‐analysis. (26th April 2013) - Bourne, C.; Aydemir, Ö.; Balanzá‐Martínez, V.; Bora, E.; Brissos, S.; Cavanagh, J. T. O.; Clark, L.; Cubukcuoglu, Z.; Dias, V. V.; Dittmann, S.; Ferrier, I. N.; Fleck, D. E.; et al.
<x xml:space="preserve">Abstract</x> Objective An association between bipolar disorder and cognitive impairment has repeatedly been described, even for euthymic patients. Findings are inconsistent both across primary studies and previous meta‐analyses. This study reanalysed 31 primary data sets as a single large sample (N = 2876) to provide a more definitive view. Method Individual patient and control data were obtained from original authors for 11 measures from four common neuropsychological tests: California or Rey Verbal Learning Task (VLT), Trail Making Test (TMT), Digit Span and/or Wisconsin Card Sorting Task. Results Impairments were found for all 11 test‐measures in the bipolar group after controlling for age, IQ and gender (Ps ≤ 0.001, E.S. = 0.26–0.63). Residual mood symptoms confound this result but cannot account for the effect sizes found. Impairments also seem unrelated to drug treatment. Some test‐measures were weakly correlated with illness severity measures suggesting that some impairments may track illness progression. Conclusion This reanalysis supports VLT, Digit Span and TMT as robust measures of cognitive impairments in bipolar disorder patients. The heterogeneity of some test results explains previous differences in meta‐analyses. Better controlling for confounds suggests deficits may be smaller than previously reported but should be tracked longitudinally across illness progression and treatment.